Diverse Expression and Distribution of ShakerPotassium Channels during the Development of the DrosophilaNervous System - Rogero, Oscar (J Neurosci, 1997)
The spatio-temporal expression of Shaker(Sh) potassium channels (Kch) in the developing and adult nervous system of Drosophila has been studied at the molecular and histological level using specific antisera.Sh Kch are distributed in most regions of the nervous system, but their expression is restricted to only certain populations of cells. Sh Kch have been found in the following three locations: in synaptic areas of neuropile, in axonal fiber tracks, and in a small number of neuronal cell bodies. This wide subcellular localization, together with a diverse distribution, implicatesSh Kch in multiple neuronal functions. Experiments performed with Sh mutants that specifically eliminate a few of the Sh Kch splice variants clearly demonstrate an abundant differential expression and usage of the wide repertoire of Sh isoforms, but they do not support the idea of extensive segregation of these isoforms among different populations of neurons. Sh Kch are predominantly expressed at late stages of postembryonic development and adulthood. Strikingly, wide changes in the repertoire of Sh splice isoforms occur some time after the architecture of the nervous system is complete, indicating that the expression of Sh Kch contributes to the final refinements of neuronal differentiation. These late changes in the expression and distribution of ShKch seem to correlate with activity patterns suggesting thatSh Kch may be involved in adaptative mechanisms of excitability.